Effects of Cell Phone Use on Caregiver Supervision and Child Injury Risk. (3rd August 2021) - Cosottile, McKenna; Damashek, Amy
Abstract: Objective: Unintentional injuries are the leading killer of children in the United States. Caregiver supervision decreases child injury risk; however, little research has examined the effects of distractions (e.g., cell phone use) on caregiver supervision and subsequent ability to protect children from injury. In particular, despite the prevalence of cell phone use, no research has examined the degree to which caregiver cell phone use may impair caregivers' ability to supervise their children effectively. The present study used a within-subjects design to examine whether caregiver cell phone use impacted caregiver vigilance and child engagement with potential hazards. Methods: A total of 51 caregiver–child dyads were observed in a pseudo hazards room across three conditions (cell phone distraction, pen-and-paper distraction, no distraction) to examine the effects of cell phone use on caregiver vigilance and child behavior (i.e., engagement with hazards) related to injury risk. Results: Caregiver vigilance was higher in the no distraction condition compared to the two distraction conditions (cell phone and pen-and-paper). Moreover, child engagement with hazards was lower in the no distraction condition than in the two distraction conditions. Although both distraction conditions impaired caregiver vigilance, caregivers were more impaired in the pen-and-paper condition compared to the cell phone condition. Discussion: Regardless the form, distracting tasks (both cell phone use and pen-and-paper task) impacted both caregiver and child behavior associated with injury risk. It is important that professionals working with parents educate them about the risks of supervising children while distracted and encourage mindful supervision to ensure safety.